Effectiveness of tertiary prevention on quality of life and control of risk factors in patients with ischemic coronary heart disease - Fernández Coronado, Rosalía (2023)
Objective. Determine the effectiveness of cardiac rehabilitation (CR) as a tertiary prevention strategy in the quality of life and control of risk factors of patients with  ischemic coronary heart disease (ICC) of the National Cardiovascular Institute (INCOR) of EsSalud- Lima during  the year 2018. Materials and methods. A retrospective cohort of 280 patients with a diagnosis of CCI was studied  who, after medical, interventional, or surgical treatment, were referred to the INCOR CR program for tertiary prevention (PT) in 2018. The program was developed according to the institutional guide for eight weeks with  exercise sessions and educational, psychological, nutritional, and recreational workshops. At the beginning and at the end of this, the QLMI-2 quality of life test was applied, and anthropometric, laboratory, and risk factor  control measurements were performed. Results. Quality of life levels at the end of CR showed a statistically significant improvement in the emotional, social, physical, and global dimensions (p < 0.001). The same behavior was observed for the nutritional variables of weight, abdominal circumference, and BMI (p < 0.001). Physical capacity showed a statistically significant improvement in the aspects of muscle strength (12.2%), physical activity (38.0%), and functional capability (25.4%) (p < 0.001). The result was not homogeneous for the biochemical metabolic variables, where glycosylated hemoglobin, glycemia, and lipid profile did not show significant improvement, except for HDL, which raised its levels statistically significantly (p < 0.001). Conclusions. CR is effective as a central strategy to perform tertiary prevention in patients with ICC since it notably improves quality of life and coronary risk factors.